Perception of effort in morning-type cyclists is lower when exercising in the morning - Kunorozva, L.; Roden, L. C.; Rae, D. E. (Journal of Sports Sciences, 2014)
A recent study found that South African endurance athletes are likely to be morning-types and carry the PER35 allele, which has been associated with a preference for mornings. The aim of this study was to measure the response of morning-type cyclists to a standardised bout of exercise performed at different times of the day. Participants ncluded 20 trained male cyclists (age: 39.8 ± 7.7 years, VO2max: 51.0 ± 7.0 ml/kg·min, training: 166 ± 98 km/wk), categorised as morning-types (mean Horne-Östberg score: 68.3 ± 5.5) and carrying the PER35 allele. They completed a 17-min sub-maximal cycling test at 60%, 80% and 90% of maximum heart rate (HRmax) at 06h00, 10h00, 14h00, 18h00 and 22h00. These morning-type cyclists reported higher ratings of perceived exertion when cycling at 60% (P = 0.044), 80% (P < 0.001) and 90% (P < 0.001) of HRmax during the evening (18h00 and 22h00) compared to the other sessions (0600, 10h00 and 14h00). This was despite absolute power output, speed and cadence displaying no time-of-day differences. Thus, morning-type cyclists perceive the same relative intensity workload to be harder in the evening compared to the morning. This may have implications for both training and competition scheduling, and highlights the importance of considering individual chronotype in sports in which diurnal variation may be relevant to training and competition.